What makes people experience flow? Social characteristics of online games. (6th September 2005) - Kim, Yong-Young; Oh, Sangjo; Lee, Heejin
Online games are games in which users play simultaneously with each other in a virtual environment. The success of online games relies on the repetitive visits of players, and thus on the very personal experiences of players. Drawing on the theory of flow, this paper empirically explores how the characteristics of online games affect the individual flow experience. Three antecedents to flow (skills, challenges and focused attention) have positive influence on the flow experience. Interactivity, whether it is human or machine, is found to influence the antecedents of the flow experience, and system performance is shown to have no or marginally significant effects. The results show that social characteristics of online games are more crucial to online game success than technological ones.